The Rhaphium crassipes species group in the Palearctic Region with the description of a new species from Uzbekistan (Diptera: Dolichopodidae) - O.P. Negrobov; I.Ya. Grichanov (Кавказский энтомологический бюллетень, 2010)
The Rhaphium crassipes species group in the Palearctic Region is defined and reviewed. It comprises 13 species including one new species. The species group is differentiated from other Rhaphium by the male mid tarsomeres 4 and 5, which are black, dilated and flattened dorsoventrally. New species Rh. samarkandiense Negrobov et Grichanov, sp. n. from Uzbekistan is described. Rh. johnrichardi Negrobov et Grichanov, nom. nov. (new name for Rh. vockerothi Negrobov, 1979 nec Robinson, 1964) is firstly described and illustrated. Rh. viklundi Grichanov, 2004 is placed in synonymy to Systenus bipartitus (Loew, 1850) (syn. n.). A key to the species group is provided, as well as new records for known species.